Xuesaitong injection treating acute myocardial infarction: A systematic review and meta-analysis. Issue 37 (17th September 2021) - Hua, Yingying; Shao, Mingjing; Wang, Yan; Du, Jinhang; Tian, Jiaxing; Wei, Kangkang; Chang, Jiangmeng; Zhang, Xiaoqiong; Chen, Ming; Liao, Jiangquan
Abstract: Background: Although the incidence of acute myocardial infarction (AMI) is decreasing, the mortality in AMI patients remains substantial. Traditional Chinese medicine has shown its role in the prevention and management of AMI. The purpose of this study is to evaluate the clinical efficacy of Xuesaitong injection (XST) for the treatment of AMI by a meta-analysis. Methods: A literature search was performed in 5 medical databases up to June 1, 2020. Randomized controlled trials involving XST combined with conventional treatment versus conventional treatment were included. A meta-analysis of clinical efficacy, left ventricular function and other objective parameters was performed to evaluate the effects of XST on AMI. Results: Five randomized controlled trials involving 539 participants were eventually included. Meta-analysis showed that the combination of XST and conventional treatment could achieve significantly better effect on improving clinical efficacy (risk ratio: 1.09 [1.01, 1.17]; P  = .04), left ventricular ejection fraction (mean difference [MD]: 3.18 [1.69, 4.67]; P  < .0001), hypersensitive C-reactive protein (MD: −2.58 [−5.04, −0.12]; P  = .04), interleukin 6 (MD: −26.00 [−38.85, −13.16]; P  < .0001), cardiac troponin T (MD: −15.85 [−18.09, −13.61]; P  < .00001) and creatine kinase myocardial isoenzyme (MD: −73.06 [−79.74, −66.37]; P  < .00001). Conclusion: XST combined with conventional treatment can achieve better efficacy on clinical performance and some of the AMI related parameters. However the interpretation of the results should be cautious, due to the relatively low quality of included trials. More rigorously designed, large-scaled, randomized controlled trials are warranted to support its clinical use in the future.